Pengembangan Bahan Ajar Teks Berita Dengan Memanfaatkan Media Video Dan Wordwall Dalam Pembelajaran Bahasa Indonesia Kelas VIII SMP YPK1 Malang - YULIANA SAFITRI; ARTIFA SORRAYA; ENDANG SUMARTI (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2024)
The purpose of this study was to develop the feasibility of teaching materials for learning Indonesian, while the teaching materials developed were wordwall-based video teaching materials for learning Indonesian, the subject matter of news texts in class VIII at SMP YPK 1 Malang. The development of news text teaching materials by utilizing video media and wordwalls is based on the irrelevance of the teaching and learning process in the classroom because the teaching staff more often use books and worksheets as learning resources so as to make the teaching and learning process look boring. The method used in developing teaching materials consists of five stages: 1) analysis, 2) design, 3) development, 4) implementation, 5) evaluation. The developed teaching materials are validated to material experts, design experts, linguists to find out the level of feasibility of the developed teaching materials in Indonesian language learning. The results of research on the development of teaching materials for news texts using video media and wordwalls in Indonesian language learning for class VIII SMP YPK 1 Malang obtained a score for the material validation results test reaching 3.30, design validation test results obtained 3.87, and language validation test results 3.11. From the values obtained according to the assessment criteria by the validator, it was stated that the teaching materials developed were included in the good criteria and deserved to be tested